Results of endoscopic management of anastomotic biliary strictures after orthotopic liver transplantation - Sinan AKAY; Zeki KARASU; Galip ERSÖZ; Murat KILIÇ; Murat AKYILDIZ; Fulya GÜNŞAR; Ulus AKARCA; Yücel BATUR; Tankut İLTER (Turkish Journal of Gastroenterology, 2019)
-